Total score of athleticism: Holistic athlete profiling to enhance decision-making - Turner, A. N.; Jones, B.; Stewart, P.; Bishop, C.; Parmar, N.; Chavda, S.; Read, P. (Strength and Conditioning Journal, 2019)
Oftentimes, the various coaching staff, sport science, and medical practitioners of a sports club require a single, holistic indication of an athlete's athleticism. Currently, there is no consensus on how this is best defined, and thus, a total score of athleticism (TSA) may provide one such method. The TSA is derived from the average of Z-scores (or T-scores in the case of small samples) from a sport-specific testing battery, ensuring athletes are judged across all the relevant fitness capacities that best define the physical demands of competition. To aid readers in using the TSA, this article also details how it is computed in EXCEL.